Metadata Aplikasi Pengurusan Dobi Berkat - Yusoff, Siti Afiqah; Aman, Hannani (Applied Information Technology And Computer Science, 2021)
This mobile application is specially developed to assist the Dobi Berkat management system. Dobi Berkat located in Kelang Lama, Kulim is a business that offers laundry services for the area nearby. This application is developed on the Android software system. The main function of this application is to allow customers to make reservations and make it easier for employees to manage the order. This function aims to improve the existing system used in the management of Dobi Berkat before this which is the manual file system. In order to develop quality applications and meet the needs of users, a prototype software model has been used in this project. There are five phases in this prototype model, namely the planning, analysis, design, implementation and testing phases and have two iterations for the analysis, design and implementation phases to produce a quality prototype. Android Studio software is used as a platform to write the code and the programming language used is Kotlin and SQLite Database is used as a database for information storage. In general, the development of this application is capable to facilitate the dealings of employees and customers to make reservations online.